Studi Simulasi: Pengaruh Soaking Time dan Injection rate Terhadap Peningkatan Recovery Factor dalam Injeksi CO2 Huff & Puff Pada Sumur X - Sahtria panjaitan, sahtria panjaitan; Triono, Agus; Eklezia Dwi Saputri, Eriska (Journal of Sustainable Energy Development, 2025)
CO₂ Huff & Puff injection is an effective enhanced oil recovery (EOR) method to boost production in declining reservoirs. This study focuses on simulating CO₂ Huff & Puff injection in Well X, SKW Field, by analyzing injection parameters such as soaking duration and injection rate. The simulation was conducted without history matching but included sensitivity analysis to evaluate reservoir performance. Seven soaking time variations (5–35 days) were tested, with 20 days yielding the highest Recovery Factor (RF) of 4.064%. Injection rate variations ranged from 1×10⁶ to 1.6×10⁶ ft³/day, with 1.4×10⁶ ft³/day achieving the highest RF increase of 4.070%. Soaking time and injection rate significantly impact oil recovery; however, excessive soaking leads to gravity segregation, reducing oil displacement efficiency. The optimal combination for maximizing recovery in Well X is a 20-day soaking time with a CO₂ injection rate of 1.4×10⁶ ft³/day. Keywords: CO2 Injection; Huff &Puff, Soaking Time, Injection rate